PERAN JARING LABA-LABA DALAM PENDEKATAN BIMBINGAN DAN KONSELING ISLAM - Syamsul, Rini; Irsyadunnas, Irsyadunnas (Al-Isyraq: Jurnal Bimbingan, Penyuluhan, dan Konseling Islam, 2025)
The concept of the spider web in the Islamic Guidance and Counseling approach as a framework for understanding the mutually supportive relationship between various dimensions of an individual's life, such as psychological, social, and spiritual. This concept emphasizes that every element of human life is interconnected, and changes in one aspect can affect other aspects. In the context of BKI, counselors are expected to view clients holistically, by considering the interrelationships between the various factors that shape their condition. This article also links the application of this concept to Islamic principles, as reflected in Surah Al-Mu'minun verse 29, which emphasizes the importance of balance and mutual support in life. With this approach, Islamic Guidance and Counseling is expected to create a safe and supportive environment, which ultimately encourages the recovery and mental, emotional, and spiritual well-being of clients.